Delectare ed prodesse: aventuras, placeres y didactismo en el Conte du Papegau - Lidia Amor (Medievalista)
When the fate of the legendary King Arthur was finally sealed, an anonymous author composed a story of his early years as sovereign. This was the first attempt – preserved up to the present – that aimed to show retrospectively Arthur’s knightly talent when facing exceptional opponents.Through the analysis of some textual marks, in this article we aim to demonstrate that the Conte du Papegau was intended for a young audience. Besides it had the purpose of providing education in the chivalrous and moral qualities expected and necessary for the youth belonging to the nobility.